Multimodal thromboprophylaxis in low-risk patients undergoing lower limb arthroplasty: A retrospective observational cohort analysis of 1400 patients with ultrasound screening. (1st June 2020) - Harrison-Brown, Meredith; Scholes, Corey; Douglas, Stephen L; Farah, Sami B; Kerr, Dennis; Kohan, Lawrence
Purpose: This study reports the results of a multimodal thromboprophylaxis protocol for lower limb arthroplasty involving risk stratification, intraoperative calf compression, aspirin prophylaxis and early (within 4 h) post-operative mobilisation facilitated by the use of local infiltration analgesia. The study also aimed to identify risk factors for venous thromboembolism (VTE) within a 3-month period following surgery for patients deemed not at elevated risk. Methods: Patients undergoing knee/hip arthroplasty or hip resurfacing were preoperatively screened for VTE risk factors, and those at standard risk were placed on a thromboprophylaxis protocol consisting of intraoperative intermittent calf compression during surgery, 300 mg/day aspirin for 6 weeks from surgery and early mobilisation. Patients were screened bilaterally for deep vein thrombosis (DVT) on post-operative days 10–14. If proximal DVT was detected, patients were anticoagulated and outcomes were recorded. Symptomatic VTE within 3 months of surgery were recorded separately. Patient notes were retrospectively collated and cross-validated against ultrasound reports. Results: At initial screening, the rate of proximal DVT was 0.54% (1.1% for knee and 0.27% for hip), and distal DVT was 6.63% (20.11% for knee and 2.31% for hip). One small, nonfatal pulmonary embolism (PE) was detected within 3 months of surgery (0.28% of total knee arthroplasty patients or 0.07% of total). All proximal DVTs were treated successfully with anticoagulants; however, one patient suffered a minor PE approximately 10 months post-operatively. Regression analysis identified knee implant and advanced age as independent risk factors for VTE in this cohort. Conclusion: Although knee arthroplasty patients remained at higher risk than hip replacement/resurfacing patients, the incidence and outcomes of VTE remained positive compared with protocols involving extended immobilisation, and episodes of PE were extremely rare. Thus, we conclude that patients at standard preoperative risk of VTE may safely be taken through the post-operative recovery process with a combination of intraoperative mechanical prophylaxis, early mobilisation and post-operative aspirin, with closer attention required for older patients and those undergoing knee surgery.